2006
DOI: 10.1093/jac/dkl257
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular killing of Brucella melitensis in human macrophages with microsphere-encapsulated gentamicin

Abstract: Altogether, these results suggest that 502H and 75:25H microspheres are suitable carriers for gentamicin targeting inside human macrophages and thus for brucellosis treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(31 citation statements)
references
References 36 publications
(38 reference statements)
1
27
0
3
Order By: Relevance
“…This is similar to the results of previously published studies entrapping gentamicin in PLGA. 12 To examine the effects of the charge of both the polymer and the drug during the formulation process, we then altered the pH of the aqueous phase from 5.0 to 7.4 and observed an approximate threefold increase in drug entrapment in PLGA nanoparticles (22.4 µg per mg PLGA, Table 1) without significant alterations to the particle diameter and zeta potential. Similarly, using an s/o/w fabrication approach, an increase in entrapment of gentamicin from 7.3 µg per mg PLGA to 21 µg per mg PLGA was observed when pH was increased from 5 to 7.4 (Table 1).…”
Section: Encapsulation Of Gentamicin In Plga Nanoparticlesmentioning
confidence: 99%
See 2 more Smart Citations
“…This is similar to the results of previously published studies entrapping gentamicin in PLGA. 12 To examine the effects of the charge of both the polymer and the drug during the formulation process, we then altered the pH of the aqueous phase from 5.0 to 7.4 and observed an approximate threefold increase in drug entrapment in PLGA nanoparticles (22.4 µg per mg PLGA, Table 1) without significant alterations to the particle diameter and zeta potential. Similarly, using an s/o/w fabrication approach, an increase in entrapment of gentamicin from 7.3 µg per mg PLGA to 21 µg per mg PLGA was observed when pH was increased from 5 to 7.4 (Table 1).…”
Section: Encapsulation Of Gentamicin In Plga Nanoparticlesmentioning
confidence: 99%
“…Gentamicin have been previously examined in a wide variety of nanoparticle delivery systems, including poly(lactide-co-glycolide) (PLGA), chitosan, and caroboxymethyldextran-b-poly(ethyleneglycols). [12][13][14] The application of antibiotic nanoparticle formulations has been shown to offer several advantages over conventional administration and delivery methods, including the ability for drug delivery to a specific site such as an intracellular infection. 15,16 Nanoparticles can also be exploited to facilitate sustained release of an antibiotic, minimizing dosing regimens.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One can also speculate that unspecific cell activation by the surfactant and synergistic enhancement of the antibiotic activity could also have exerted some antibacterial effect. PLGA 502H microparticles prepared by the solvent evaporation method were further used against B. melitensis infected human macrophages (91). The results demonstrated that these PLGA microparticles are efficiently captured by the macrophages and that the gentamicin released from these particles is active and can exert its bactericidal effect inside the macrophagic cells.…”
Section: In Vitro Efficacy Of Polymeric Particles For Antibiotic Treamentioning
confidence: 99%
“…Sistemas nanoparticulados têm sido propostos para a internalização de agentes antimicrobianos no ambiente intracelular, contribuindo assim para aumentar o índice terapêutico de antimicrobianos nos locais das infecções (Lecároz et al 2006).…”
Section: Introductionunclassified